Committee decisions impact on the World Heritage List: breaking the balance - Zunjic, Iva (Protection of Cultural Heritage, 2023)
This paper represents a part of my PhD study which aims to identify anomalies in the procedure of inscribing properties on the World Heritage List through a comparative study of the recommendations of the advisory bodies and of the final decisions taken by the World Heritage Committee between 2010 and 2019 and how they indirectly affect the credibility and the future of the 1972 Convention Concerning the Protection of the World Cultural and Natural Heritage. How is the procedure evolving and what distortions can be identified between the stated principles and the inscriptions on the List? How does this influence the evolution of the World Heritage List and the concept of the Outstanding Universal Value (OUV)?